Preliminary Study: RFID-Based Computer Vision Technology Prototype as Information Management Systems in the Logistics Industry - Ar-Rafi, Ahmad Reza; Permana, Enda; Okitasari, Hanissa (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to fill this gap by evaluating the benefits and challenges of applying CVT to a prototype monitoring camera, as well as developing an optimal implementation strategy. Research Design and Methodology: Through a mixed-methods approach and black-box testing, the results show that the application of CVT has great potential to revolutionize industrial IMS, particularly in aspects such as real-time monitoring, visual data analysis, and decision-making. Findings and Discussion: The preliminary results suggest that this technology can improve operational efficiency, accuracy, and safety, thereby enhancing productivity and cost efficiency. Implications: This research explores the potential contribution of CVT to IMS in the industrial sector, focusing on the use of a prototype Radio Frequency Identification (RFID)-based monitoring camera, and examines its long-term implications.